Oxford Studies in Early Modern Philosophy, 4. - Garber, Daniel, 1949- (OUP Oxford, 2008)
Oxford Studies in Early Modern Philosophy presents a selection of the best current work in the history of early modern philosophy. It focuses on the seventeenth and eighteenth centuries - the extraordinary period of intellectual flourishing that begins, very roughly, with Descartes and his contemporaries and ends with Kant. - ;Oxford Studies in Early Modern Philosophy is an annual series, presenting a selection of the best current work in the history of early modern philosophy. It focuses on the seventeenth and eighteenth centuries - the extraordinary period of intellectual flourishing that be.